2016
DOI: 10.1016/j.clinph.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Sequential processing in young and older adults in the equiprobable auditory Go/NoGo task

Abstract: Objective: We recently proposed a sequential processing schema for the equiprobable auditory Go/NoGo task, based on a principal components analysis (PCA) of event-related potentials (ERPs) from a university student sample. Here we sought to replicate the schema, and use it to explore processing in well-functioning older adults. Methods: We compared behavioural responding and ERPs of 20 independent-living older adults (M age = 68.2 years) to data from a sex-and handedness-matched group of university students (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
40
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 46 publications
9
40
2
Order By: Relevance
“…In temporal order, based on their latency, scalp topography, and similarity to components in previous fixed SOA studies De Blasio, 2013, 2015;Barry et al, 2014aBarry et al, , 2014bBarry et al, , 2014cBarry et al, , 2016, these components were identified as N1-1, PN, a P2/N2b complex, N2c, P3, SW, and LP. Fig.…”
Section: Empirical Pca Outcomesmentioning
confidence: 69%
See 4 more Smart Citations
“…In temporal order, based on their latency, scalp topography, and similarity to components in previous fixed SOA studies De Blasio, 2013, 2015;Barry et al, 2014aBarry et al, , 2014bBarry et al, , 2014cBarry et al, , 2016, these components were identified as N1-1, PN, a P2/N2b complex, N2c, P3, SW, and LP. Fig.…”
Section: Empirical Pca Outcomesmentioning
confidence: 69%
“…We expected that a Combined PCA, following our standard procedure and inputting ERPs from both Go and NoGo conditions, would replicate the previous young adult schema studies (Barry and De Blasio, 2013;Barry et al, 2014aBarry et al, , 2014bBarry et al, , 2014cBarry et al, , 2016. In contrast, we expected Separate PCAs, conducted independently on each of the Go and NoGo ERP sets, to yield components similar to those identified in the processing schema, but with latency shifts that reflected differences such as those apparent between P3a and P3b in the raw ERPs.…”
Section: The Present Studymentioning
confidence: 86%
See 3 more Smart Citations